Use of a palladium catalyst to improve the capacity of activated carbon to absorb ethylene, and its effect on tomato ripening - Bailen, G.=700 1 Guillen, F.; Castillo, S.; Zapata, P.J.; Serrano, M.
Es, En)
Ilus., 21 ref.
Keywords: ADSORCION; ETILENO; CARBON ACTIVADO; CALIDAD; LYCOPERSICON ESCULENTUM; ACTIVIDAD CATALITICA; REACCIONES QUIMICAS; ESPAÑA